PENGARUH PEMBERIAN EKSTRAK JAHE MERAH (Zingiber officinale var. Rubrum) TERHADAP JUMLAH SEL MAKROFAG ULKUS TRAUMATIKUS MUKOSA MULUT AKIBAT BAHAN KIMIAWI Penelitian in vivo pada Rattus Norvegicus - Fitria Hidayati; Prima Agusmawanti; Muhammad Dian Firdausy (Odonto : Dental Journal, 2015)
Background: Traumatic ulcer is an oral mucosa ulcerative lesion caused by trauma. One of the causes is chemicals. Clinical features of traumatic ulcer including yellowish white spots with reddish halo and painful. Treatment for this ulcer are suppressing inflammation and pain thus will increase healing process. Macrophage will be decreased at the end of the inflammatory phase. Red ginger extracts (Zingiber officinale var. Rubrum) contains some compounds that can heal ulcers. Purpose: The objective of this research was to find out the effect of red ginger extract on the macrophage numbers in traumatic oral mucosal ulceration due to chemical in Rattus norvegicus. Method: This study was experimental which post test only control group design. There were five groups: negative control group without intervention, positive control group treat aloclair, and red ginger extract in 2%, 4%, 8% consentration group. The experimental animals were used 25 Rattus norvegicus. They were injured on oral mucosa using H2O2 30% two times a day. Their oral mucosa were made as hystologycal slide, and macrophage counts were observed, then analyzed by Anova test and LSD test. Result: The result indicates some significant effect of red ginger extract on the macrophage numbers in traumatic oral mucosal ulceration from Anova test 0,001 (<0,05). There are significant differences between 2% consentration of red ginger extract and positive control group.There are no significant difference beetween 4%, 8% consentration of red ginger extract and positive control group. Conclusion: It can be concluded that red ginger extract have influence on the number of macrophages in chamical traumatic oral mucosal ulceration in Rattus norvegicus.